An Analysis of the Technology Acceptance Model in Understanding The University of Jordan’s Students Behavioral Intention To Use m-Learning - FALAH, JANNAT; ALFALAH , SALASABEEL F. M.; ALFALAH, TASNEEM; QUTECHATE, WALAA; AYYOUB, HANI; MUHAIDAT, NADIA (International Journal of Psychosocial Rehabilitation, 2020)
The recent advances in mobile technology, and the associated ability to access information instantly without the need to refer to a computer device, has led to increasing popularity of this type of technology in all areas of modern life. Is it not surprising therefore, that using mobile applications is growing increasingly appealing in the field of education. Learning Management Systems (LMSs) are moving towards including mobile application to enable on the go access to their users. This paper was designed to investigate The University of Jordan’s (JU) students’ intentions towards the usage of mobile technologies, and their willingness to adopt mobile application learning management system. Technology Acceptance Model (TAM) is a strong theoretical tool to understand users’ acceptance of Mobile Learning (m-learning). The model which included m-learning self- efficacy, subjective norm, system accessibility, perceived usefulness, perceived ease of use, attitude toward usage, and behavioral intention to use m-learning, was developed based on the extended technology acceptance model. This study analyzed the relationships among factors predicting mobile learning management system (m-LMS); data from 1199 students in JU were collected to investigate integrated relationships among constructs in TAM. In line with previous studies original TAM hypotheses were supported. Furthermore, the external variables: self-efficacy, subjective norm, and system accessibility have a significant influence on perceived usefulness, perceived ease of use, attitude toward usage and intention to use.